Westerbork Girl - Oord, Steffie van den (Netherlands : Orthel, Rolf, 2007)
In Westerbork, Hannelore Cahn was the star of the camp variety theatre. Singing and dancing seemed to protect her from deportation to Auschwitz. Her beauty and her girlish charm turned heads, including that of the Viennese Jewish camp policeman Hans Eisinger. Hannelore found his Austrian accent charming, but her great love was the Jewish actor Rob de Vries, whom she had met during the early days of the war. In 1943, Rob de Vries freed Hannelore spectacularly from Westerbork. A week after her escape she returned voluntarily to the camp, to Hans Eisinger, who later became her husband. Now 83 years old, Hannelore tells her story of survival and love, forgetting and remembering, and ponders the decision that still haunts her today.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films